“I Chose Some Cups and Saucers”: Gender, Tradition, and Subversive Elements in my Grandmother’s Life Stories - Buhler, Sarah (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
This article is a feminist analysis of the oral life stories of the author’s Mennonite grandmother, Maria Buhler. By using gender as a category of analysis, the author demonstrates that the stories tend to simultaneously subvert and reinforce traditional Mennonite women’s gender roles. The author discusses implicit and explicit references to the dynamics of gender in the stories, and thereby uncovers subtexts and meanings valuable for a feminist understanding of Mennonite women’s lives and history. Various performance tactics used by Maria Buhler in the telling of her stories are also considered. A feminist reading of the stories sheds light on the traditional gender role and identity embraced by Maria Buhler, as well as upon Maria Buhler’s subtle challenges to male dominated versions of Mennonite history and tradition.